OBJETIVIDAD JURÍDICA, ANTIRREALISMO E INTERPRETATIVISMO. LA VISIÓN REALISTA DE MICHAEL S. MOORE - García Rivera, Paola (Revista de Derecho, 2022)
This paper has endeavoursed establish the question of legal objectivity as part of the philosophical debate between realism, antirealism and interpretivism. With this aim, it was exposed the relationship between realism and legal objectivity established by Michael S. Moore. For this author, realism is the path to overcome all the skepticist orientation in law, which weakens the sense of objectivity by denying the independence of reality from the mind and convention.